EKSISTENSI PERADILAN ADAT PADA SISTEM HUKUM PIDANA DI INDONESIA DALAM UPAYA PEMBAHARUAN HUKUM PIDANA NASIONAL - Hamdani, Surya; Ningrum, Annisa Danti Avrilia; Muammar, Muammar (Jurnal Ilmu Hukum Reusam, 2024)
Although formally customary judiciary institutions are not yet included in the scope of general justice, in reality this mechanism is another alternative that is often pursued by justice seekers, especially in societies that are still based on traditional patterns of life with the norms that constitute them. The sense of justice that is not fulfilled by the formal legal system can sometimes be fulfilled by the customary justice mechanism. The research method uses the normative juridical method with an emphasis on literature study. analysis is carried out on legal norms, both law in statutory regulations and law in court decisions). The conclusion of this research is that the existence of Customary Law Courts in the legal system in Indonesia is very important to provide solutions to legal problems in general that intersect with the interests of the stakeholders of the Indigenous people and the Indigenous Peoples themselves. The basis for the existence of Adat Justice has been recognized for its existence in the Legal System in Indonesia which can be traced to its existence from several existing laws and regulations.